Arts-Based Methods in Refugee Research Creating Sanctuary - Lenette, Caroline (Springer Nature Singapore : Imprint: Springer, 2019)
Drawn from a decade of refugee studies, this book offers a wealth of insights on arts-based methodologies. It explores exciting new prospects for participatory and culturally safe research, and will be a reference resource for researchers of all levels and community practitioners. The book tackles questions of meaningful research practice: How do people with lived experiences of forced migration-Knowledge Holders-lead the way? Can arts-based methods bring about policy and social change? And what of ethical issues? By reflecting on the strengths and limitations of four research methods (digital storytelling, photography, community music, and participatory video), readers are invited to craft their own approach to arts-based projects.